DETERMINAN PERTUMBUHAN EKONOMI DI DKI JAKARTA - Avivah Isnaini; Hadi Sasana (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2022)
This study aims to analyze the short-term and long-term relationship of the number of workers, HDI, inflation and investment to economic growth in DKI Jakarta Province. The research method used is ECM using time series data with a time period of 1991-2020 or 30 years. The findings revealed that the number of workers does not affect the economic growth of the DKI Jakarta Province in the short term, but in the long term the number of workers has an effect on the economic growth of the DKI Jakarta Province. Likewise, HDI does not affect the economic growth of DKI Jakarta Province in the short term and long term. Inflation in the short term and long term does not affect the economic growth of DKI Jakarta Province. Meanwhile, investment affects the economic growth of DKI Jakarta Province both in the short and long term.